RHETORICAL DEVICES IN ADVERTISING SLOGANS: A COMPETITIVENESS VIEWPOINT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Due to increasing amount of competition as well as a colossal amount of information people come across, nowadays are needed such advertisements that leave a strong impression on potential customers. Previous research has suggested rhetoric can be used to make ads more competitive. The aim of this report is to comment on the usage, as well as the effectiveness of rhetorical figures in advertising. A sample of 815 advertising slogans was gathered from various Bulgarian media. The slogans were analyzed for the presence or absence of rhetorical figures. The results of the study indicate that rhetorical devices are frequently employed when creating advertising slogans. The most commonly used rhetorical figures are metaphor, epithet and appeal. The product categories in which rhetorical devices are most frequently applied are Foods, Beverages and Fashion. The retailing sector is the only one in which fewer than half of the examined slogans rely on the usage of rhetoric. To assess the effectiveness of rhetoric in advertising, an online survey was developed. Three hundred respondents participated. They were asked to evaluate three pairs of advertising slogans. In each of these pairs, the first slogan was taken in its original form - containing a rhetorical device. The second slogan was transformed in such a manner that the rhetorical figure was removed, while the meaning of the slogan was preserved. The respondents had to assess the slogans according to seven criteria. According to the results of this study, the usage of rhetorical figures increases slogans’ perceived persuasiveness, creativity, pleasantness, comprehensibility and memorability. The employment of rhetorical devices increase the competitiveness of advertising communication.